Species diversity and utilization of bamboo to support life’s the community of Karangwangi Village, Cidaun Sub-District of Cianjur, Indonesia - HAILU WELDEKIROS HAILU; SAJIDAN SAJIDAN; ARTINI PANGASTUTI; RALF GREINER (Biodiversitas Journal of Biological Diversity, 2017)
Abstract. Hailu HW, Sajidan, Pangastuti A, GreinerR. 2017. Isolation, characterization and 18S rDNA sequence analysis of phytase producing fungi from Indonesia, Indonesia. Biodiversitas 18: 10-14. Phytase breaks down the phytate portion of grains and oil seeds; thereby, releasing phosphorus and minerals for animals. The objectives of this research were to screen phytase-producing novel species of fungi; to conduct cultural and phylogenetic characterization; to perform 18S rDNA sequencing and BLAST analysis. Samples of fungi were collected from different sources, cultured on potato dextrose agar and potato dextrose broth. Phytase assay was conducted based on Vanadate-molybdate method. Three isolates with highest enzyme activity were selected for pH and temperature optimization. DNA was extracted by modifying plant DNA extraction and yeast genomic DNA extraction kits. The 18S rDNA gene was amplified and sequenced. The result indicated that optimum temperatures ranged from 60-75oC and the optimum pH for isolates from papaya (Angr), palm bark (Abark) and sugarcane soil field (Asoil) were 4.5, 3.0 and 4.5, respectively. Based on 18S rDNA sequence analysis the phytase producing fungal isolates Angr, Abark and Asoil were identical to Aspergillus niger, Beauveria felina and Nigrosabulum globosum, respectively.Keywords: 18S rDNA, BLAST, fungi, phytase, phylogeny